Climate Smart Agriculture in South Asia: Technologies, Policies, and Digital Innovation for South Asian Association for Regional Cooperation (SAARC) Member Countries - Gakhar, Shalini; Sharma, Sheetal; Patwar, Shelly (2023)
SAARC Agriculture Centre (SAC) and International Rice Research Institute (IRRI) organized a four-day training program for SAARC member countries representatives on Climate Smart Agriculture in South Asia: Technologies, Policies, and Digital Innovation. 28 senior government officials and high-ranking country representatives from Bangladesh, Bhutan, India, Maldives, Nepal, and Sri Lanka participated in this training program. The details of the participants are presented in Annexure 4. The program served as a strategic initiative to foster sustainable agricultural practices and address the challenges posed by climate change.